The impact of CEO Power on Financial Performance Moderated by CSR - habib anugrah, pandu; Fenny Marietza (Jurnal Ekonomi, 2024)
The objective of this investigation is to scrutinize the impact of CEO Power on the financial performance, taking into account the potential influence of CSR within the manufacturing sector of Indonesian companies spanning from 2018 to 2020. This study aims to fill an empirical void identified in previous exploration by re-examining the Interrelation between CEO Power also financial performance through the lens of agency theory. What sets this exploration apart is the introduction of Corporate Social Responsibility (CSR) as a moderating variable in the CEO's influence on financial performance. The analytical approach employed is multiple linear regression, complemented by moderation variable analysis (MRA) using Eviews software. The outcomes reveal that CEO Power does not exert a significant impact on financial performance, also the role of CSR neither reinforces nor diminishes the impact of CEO Power on financial performance.